AKTIVITAS ANAK JALANAN PEREMPUAN DI KOTA PEKANBARU - Rammadani, Dwi Cahyo; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The survey in 2018 found there were 115 female street children in Pekanbaru which worked with various types of jobs, such as selling tissue, newspapers, buskers, and so on. They have different backgrounds, some of them dropouts and some are still students. The subject in this study is the children aged 6-18 years and more than 7 hours a day. The author used accidental and purposive sampling techniques to determine the subject and from this method, 6 subjects were identified with jobs including newspaper traders, tissue traders, street vendors, and buskers. The results found that street children in Pekanbaru based on their intensity can be categorized as Vulnerable Children to Be Street Children and based on field studies can be referred to Children of the Street. The motive or reason for the subject to become a street child is due to his own desire to help the family economy and influence of friends or social environment. They work more than 7 hours a day, move around the work location, and sometimes don't just sell one type of ite.                                                                              Key words: Street Children, Girls, Poverty